2022
DOI: 10.3390/biomedicines10010193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alirocumab on Triglyceride Metabolism: A Fat-Tolerance Test and Nuclear Magnetic Resonance Spectroscopy Study

Abstract: Background: PCSK9 antibodies strongly reduce LDL cholesterol. The effects of PCSK9 antibodies on triglyceride metabolism are less pronounced. The present study aimed to investigate in detail the effects of alirocumab on triglycerides, triglyceride-rich lipoproteins, and lipase regulators. Methods: A total of 24 patients with an indication for treatment with PCSK9 antibodies were recruited. There were two visits at the study site: the first before initiation of treatment with alirocumab and the second after 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Indeed, circulating PCSK9 remains bound to the therapeutic antibody for 2 to 3 weeks [ 31 ]. Nevertheless, total serum PCSK9 levels increased approximately 10-fold after 6 months of treatment with PCSK9 inhibitors, similar to previous studies [ 31 , 32 ]. Studies measuring only free circulating PCSK9 (without inactive PCSK9 bound to the therapeutic antibody) showed a decrease in PCSK9 levels after treatment with PCSK9 inhibitors [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, circulating PCSK9 remains bound to the therapeutic antibody for 2 to 3 weeks [ 31 ]. Nevertheless, total serum PCSK9 levels increased approximately 10-fold after 6 months of treatment with PCSK9 inhibitors, similar to previous studies [ 31 , 32 ]. Studies measuring only free circulating PCSK9 (without inactive PCSK9 bound to the therapeutic antibody) showed a decrease in PCSK9 levels after treatment with PCSK9 inhibitors [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, preliminary results from the ALIROCKS study reported that total plasma PCSK9 levels could serve as a biomarker for adherence to treatment with PCSK9 antibodies. They suggested that in non-adherent patients, LDL-C levels should decrease by no more than 25% and total PCSK9 levels should increase by no more than threefold after treatment with PCSK9 inhibitors [ 32 ]. Based on these criteria, we identified three non-adherent patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted-average lipoprotein particle sizes are derived from the sum of the diameter of each subclass multiplied by its relative mass percentage based on the amplitude of its methyl NMR signal [ 4 ]. The Numares AG (Am Biopark 9, 93053 Regensburg, Germany) performed NMR analysis using the AXINON ® lipoFIT ® method (in the further text briefly lipofit) in Regensburg with an Avance III HD nuclear magnetic resonance spectrometer (Bruker; Billerica, MA, USA), an Ascend 600 MHz magnet (Bruker), and using TopSpin 3.2 (Bruker) and Axinon Suite 1.0.0.1 (Numares, Regensburg, Germany) software [ 12 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The influence of alirocumab (PCSK9 antibodies) treatment on the metabolism of triglycerides was studied, with no significant effects being found on the levels of fasting triglycerides, post-prandial triglycerides, or proteins related to the regulation of lipoprotein lipase [26]. The short-term influence of alirocumab on vascular function has been studied, with no significant changes observed in the thickness of the carotid intima-media, brachial artery flow-dependent dilatation, or carotid artery fractional anisotropy [27].…”
mentioning
confidence: 99%